Histopathological correlations and fat replacement imaging patterns in recessive limb‐girdle muscular dystrophy type 12 - Bram De Wel; Lotte Huysmans; Christophe E. Depuydt; Veerle Goosens; Ronald Peeters; Filipa P. Santos; Dietmar R. Thal; Patrick Dupont; Frederik Maes; Kristl G. Claeys (Wiley, 2023)
Abstract Background Despite the widespread use of proton density fat fraction (PDFF) measurements with magnetic resonance imaging (MRI) to track disease progression in muscle disorders, it is still unclear how these findings relate to histopathological changes in muscle biopsies of patients with limb‐girdle muscular dystrophy autosomal recessive type 12 (LGMDR12). Furthermore, although it is known that LGMDR12 leads to a selective muscle involvement distinct from other muscular dystrophies, the spatial distribution of fat replacement within these muscles is unknown. Methods We included 27 adult patients with LGMDR12 and 27 age‐matched and sex‐matched healthy controls and acquired 6‐point Dixon images of the thighs and T1 and short tau inversion recovery (STIR) MR images of the whole body. In 16 patients and 15 controls, we performed three muscle biopsies, one in the semimembranosus, vastus lateralis, and rectus femoris muscles, which are severely, intermediately, and mildly affected in LGMDR12, respectively. We correlated the PDFF to the fat percentage measured on biopsies of the corresponding muscles, as well as to the Rochester histopathology grading scale. Results In patients, we demonstrated a strong correlation of PDFF on MRI and muscle biopsy fat percentage for the semimembranosus (r = 0.85, P < 0.001) and vastus lateralis (r = 0.68, P = 0.005). We found similar results for the correlation between PDFF and the Rochester histopathology grading scale. Out of the five patients with inflammatory changes on muscle biopsy, three showed STIR hyperintensities in the corresponding muscle on MRI. By modelling the PDFF on MRI for 18 thigh muscles from origin to insertion, we observed a significantly inhomogeneous proximo‐distal distribution of fat replacement in all thigh muscles of patients with LGMDR12 (P < 0.001), and different patterns of fat replacement within each of the muscles. Conclusions We showed a strong correlation of fat fraction on MRI and fat percentage on muscle biopsy for diseased muscles and validated the use of Dixon fat fraction imaging as an outcome measure in LGMDR12. The inhomogeneous fat replacement within thigh muscles on imaging underlines the risk of analysing only samples of muscles instead of the entire muscles, which has important implications for clinical trials.